ANALISIS PERBANDINGAN RESIKO KEUANGAN BANK PERKREDITAN RAKYAT (BPR) PERSEROAN TERBATAS DAN BPR KOPERASI - MIKNYO JADMIKO, ANDREAS Miknyo (Jurnal Akuntansi AKUNESA, 2013)
This study aims to analyse and compare the financial risk on two BPR withdistinct legal entity . Consist of BPR with legal entity of “Perseroan Terbatas” andBPR with legal entity of “Koperasi” . This study uses two samples, namely BPRPerseroan Terbatas "PT" and BPR Koperasi "KOP". Analysis using the Z-Scoremethod (discriminant analysis). The analisys result shows the level of financial riskof each BPR.Keyword : Z-score, Financial Risk, BPR.